2018
DOI: 10.1123/jsr.2016-0100
|View full text |Cite
|
Sign up to set email alerts
|

Lower-Extremity Muscle Activity, Kinematics, and Dynamic Postural Control in Individuals With Patellofemoral Pain

Abstract: There were alterations in muscle activity during SEBT performance, suggesting that overactivity of AL relative to GMED is a unique neural recruitment pattern in those with PFP. However, hip and knee joint kinematics did not seem to contribute to deficits in the anterior reach distance, suggesting a need for continued assessment of these deficiencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Also, the most important results from the kinetic parameters mentioned in the study by Arazpour et al [26] included increase contralateral pelvic drop and hip adduction reduce knee extensor moment and delayed peak rear foot eversion during gait (Tables 2 and 3). The finding of this study demonstrated that knee valgus displacement was significantly increased in subjects with PFPS compared to healthy subjects 68 H Goto et al [2] Case-control 14 PFP Hip flexion/adduction/internal rotation They found that there is no significant difference between kinematic parameters in patients with patella femoral pain syndrome compared to healthy subjects (p>0.05) 14 H Knee flexion/abduction/internal rotation Table 3: New studies investigating the effects of patella femoral pain syndrome on gait parameters.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…Also, the most important results from the kinetic parameters mentioned in the study by Arazpour et al [26] included increase contralateral pelvic drop and hip adduction reduce knee extensor moment and delayed peak rear foot eversion during gait (Tables 2 and 3). The finding of this study demonstrated that knee valgus displacement was significantly increased in subjects with PFPS compared to healthy subjects 68 H Goto et al [2] Case-control 14 PFP Hip flexion/adduction/internal rotation They found that there is no significant difference between kinematic parameters in patients with patella femoral pain syndrome compared to healthy subjects (p>0.05) 14 H Knee flexion/abduction/internal rotation Table 3: New studies investigating the effects of patella femoral pain syndrome on gait parameters.…”
Section: Resultsmentioning
confidence: 57%
“…Patellofemoral pain syndrome (PFPS) is one of the disorders that are related to the knee joint which includes 10 to 25 percent of knee injuries [1,2]. The incidence of this complication is estimated to be between 7% and 15% in young adults in military [3].…”
Section: Introductionmentioning
confidence: 99%
“…At this stage, the patient lied on his back on the examination table and the distance between the anterior superior iliac spine up to malleus internal was recorded a s the lower limb length. This evaluation was performed for both limbs [14].…”
Section: Plain Language Summarymentioning
confidence: 99%
“…The calibration of the HHD was established before the study by placing a specific weight on the HHD and comparing it with the weight indicated by it [22]. Before running the experiment, the study patients performed two sub-maximal contractions to become familiarized with the method [14].…”
Section: Plain Language Summarymentioning
confidence: 99%
See 1 more Smart Citation